ANALISIS ALTERASI DAN MINERALISASI MENGGUNAKAN METODE XRD, PETROGRAFI DAN MINERAGRAFI DAERAH PROSPEK CIHAUR, SIMPENAN, KABUPATEN SUKABUMI: ALTERATION AND MINERALIZATION ANALYSIS USING XRD, PETROGRAPHY AND MINERAGRAPHY METHODS, CIHAUR PROSPECT AREA, SIMPENAN, SUKABUMI REGENCY - Finlandini, Nadya; Joko Suprapto, Sabtanto; M I Shiddiq, Asep; Novalia, Lia; Syafrudin Anshar, Muhammad (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2024)
The research is located in Cihaur, Sukabumi, West Java, occupied by the Jampang Formation, located in the Sunda-Banda Arc. The magmatic activity and complex tectonic setting in the arc have the potential to cause mineralization, resulting in several types of ore deposits such as porphyry, epithermal and skarn. The objectives of this research are to identify alteration, mineralization, and ore deposit types in the research area. The research methodology includes exploration drilling, alteration mapping, and laboratory analysis using XRD, petrography, and mineragraphy methods. Alteration of the research area consists of argillic alteration (illite, kaolin, and smectite), propylitic alteration (chlorite, epidote, and calcite), marbellized (95% calcite), and skarnization (clinopyroxene, wollastonite, chlorite-skarn, and epidote-skarn). In the skarn there are indications of a prograde stage characterized by pyroxene and wollastonite minerals, and a retrograde stage characterized by epidote, calcite, and chlorite minerals. Mineralization of the research area consists of galena, sphalerite, pyrrhotite, pyrite, and chalcopyrite. The presence of pyroxene and wollastonite minerals, as well as galena and sphalerite indicate that the skarn formed in the intermediate to distal zone.